Maternal diabetes mellitus and congenital malformation. Survey of 205 cases. Issue 12 (December 1976) - Day, R E; Insley, J
Abstract : Twenty-five out of 205 (i.e. 12%) babies born to diabetic mothers in the Birmingham Maternity Hospital in the period 1969-1974 were malformed as against 6% in a control group. The incidence was highest in the group where mothers were on insulin at the time of conception (17 out of 117, i.e. 15%). No correlation was observed between major malformation in this group and age of onset or duration of the diabetes, progressive vascular complications, maternal age, or parity. Cardiovascular malformations were over-represented.